The Importance of mTOR Trafficking for Human Skeletal Muscle Translational Control - Hodson, Nathan (Exerc Sport Sci Rev, 2019)
The mechanistic target of rapamycin (mTOR) is a central regulator of muscle protein synthesis, and its activation has long been attributed to its translocation to the lysosome. Here, we present a novel model of mTOR activation in skeletal muscle where the translocation of mTOR and the lysosome toward the cell membrane is a key process in mTOR activation.